Da competição à cooperação entre cidades : consórcio público como instrumento de política urbana e gestão metropolitana de transportes : caso da Região Metropolitana da Grande Vitória (RMGV-ES) - Lemos, Claudia Rodrigues Tozetti (2011)
The restructuring processes of the territory of contemporary cities associated with economic, political and social changes, with the growth and transformation of structure and urban manner significantly alters the current everyday urban practices. The sum